Dissecting Efficacy and Metabolic Characteristic Mechanism of Taxifolin on Renal Fibrosis by Multivariate Approach and Ultra-Performance Liquid Chromatography Coupled With Mass Spectrometry-Based Metabolomics Strategy - Ren, Lei; Guo, Hao-Nan; Yang, Jun; Guo, Xiao-Ying; Wei, Ye-Sheng; Yang, Zhao (Frontiers in Pharmacology, 2021)
Taxifolin (TFN) is an important natural compound with anti-fibrotic activity, however, its pharmacological mechanism is not clear. In this study, we aimed to insight into the effects of TFN and its potential mechanisms in unilateral ureteral obstruction (UUO) animal model using metabolomics approach to identify the metabolic biomarkers and perturbed pathways. Serum metabolomics analysis by UPLC-Q-TOF/MS was carried out to discovering the changes in the metabolic profile. It showed that TFN has a significantly protective effect on UUO-induced renal fibrosis and a total of 32 potential biomarkers were identified and related with RF progression. Of note, 27 biomarkers were regulated by TNF treatment, which participating in eight metabolic pathways, including phenylalanine, tyrosine and tryptophan biosynthesis, phenylalanine metabolism, etc. It also showed that metabolomics was promising strategy to better dissecting metabolic characteristic and pharmacological mechanism of natural compounds by multivariate approach and ultra-performance liquid chromatography coupled with mass spectrometry.